(untitled) (South East Asia Journal of Public Health, 2015)
A large number of epidemiological studies reported an increase in mortality due to cancer and other diseases among lean individuals. In this paper we aimed to investigate the relationship between smoking status and Body Mass Index (BMI) in men aged 20 years and above. A cross sectional study was conducted in the rural field practice area of the Department of Community Medicine, PSG Institute of Medical Science and Research, Coimbatore during June and July 2010. A total of 459 men aged 20 years and above were included in the study. Statistical analyses were done using the General Linear Model procedure of SPSS. We observed that cigarette smokers weighed (Kg) less, p<0.01 (age adjusted mean ± standard error= 58.64±0.44) and were leaner, p<0.001 [age adjusted mean BMI (kg/m2) ± standard error=21.13±0.13] than ex/non-smokers (61.11±0.69 and 22.19± 0.2 respectively). Regarding the intensity of smoking and BMI, light smokers (1 to 20 cigarettes per day) were leaner than ex/non smokers (mean ± standard error were 21.13 ± 0.13, 22.19 ± 0.208 respectively, p< 0.001). Regarding the duration of smoking and BMI, a linear diminution in BMI is observed with increasing duration of cigarettes smoking compared to ex/non smokers (mean ± standard error of BMI) for ex/non smokers 22.19±0.208, 1 to 10 years of smoking 21.56 ± 0.221(p<0.05); 11 to 20 years of smoking 21.23±0.256 (p<0.01); 21 to 30 years of smoking 20.30 ± 0.333 (p<0.001); 30 and above years of smoking 20.07±0.501 (p<0.001). In conclusion, we found significant results confirming an association between cigarette smoking and lower BMI in men. Hence we recommended that health intervention programs to quit smoking should take into account the underlying perceived benefits of smoking with body weight. DOI: http://dx.doi.org/10.3329/seajph.v4i1.21841 South East Asia Journal of Public Health Vol.4(1) 2014: 53-58